2004
DOI: 10.1002/clc.4960270307
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral arterial tonometry: A diagnostic method for detection of myocardial ischemia induced during mental stress tests: A pilot study

Abstract: Background: Mental stress testing is considered a reliable method for diagnosing patients with coronary heart disease (CHD) who may be at risk for future events. It has been shown recently that myocardial ischemia induced during mental stress tests is speciFICAlly associated with peripheral arterial vasoconstriction.Hypothesis: The study was undertaken to test the diagnostic capability of peripheral arterial tonometry (PAT) to detect peripheral arterial vasomotor changes.Methods: We monitored pulsatile finger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 28 publications
0
47
0
Order By: Relevance
“…Subjects were lying down supine comfortably with legs uncrossed, in a quiet, temperature-controlled room. A fitted blood pressure cuff was placed on one arm, and the PAT was performed as previously published and validated [21, 22] [23, 24]. …”
Section: Methodsmentioning
confidence: 99%
“…Subjects were lying down supine comfortably with legs uncrossed, in a quiet, temperature-controlled room. A fitted blood pressure cuff was placed on one arm, and the PAT was performed as previously published and validated [21, 22] [23, 24]. …”
Section: Methodsmentioning
confidence: 99%
“…92 Moreover, Goor et al has demonstrated that there is a characteristic PAT signal response to mental stress, with diminution of the signal amplitude during stress. 90 However, this test is only thought to be partially dependent on NO, 93 with other factors such as the sympathetic nervous system thought to affect the microvascular response to certain stimuli. 94 There are discordant reports as to the agreement between FMD and PAT as some reports highlight a discordance with PAT and FMD measurements, 95,96 while others find an association between the two tests.…”
Section: 80mentioning
confidence: 99%
“…32,39,44,7880 In multiple studies, the response mental stress testing was shown to have significant prognostic value in cardiac diseases and future cardiac events.…”
Section: Clinical Assessment Of Endothelial Functionmentioning
confidence: 99%